Direct and indirect impacts of pumping station operation on downstream migration of critically endangered European eel. (8th October 2018) - Bolland, Jonathan D.; Murphy, Leona A.; Stanford, Robert J.; Angelopoulos, Natalie V.; Baker, Nicola J.; Wright, Rosalind M.; Reeds, Jake D.; Cowx, Ian G.
Abstract: Downstream passage of European eel Anguilla anguilla (L.) in catchments with pump(s) for water level management is a major concern. Catchment‐wide acoustic telemetry revealed silver eels quickly migrated downstream through unobstructed reaches ( n = 12; mean ± SD = 17.9 ± 1.9 km/day). Fourteen of 17 acoustic‐tagged eels detected at the pumping station (82.1%) retreated back upstream and ten (58.8%) passed through pumps after delays (9.5 ± 11.0 days). Multi‐beam sonar imaging across the intake screen (55‐mm gaps) revealed that peaks in migration occurred during the nights preceding the new moon but 76.7% retreated back upstream. All passive integrated transponder (PIT)‐tagged eels recaptured ( n = 56) downstream of a large (2.23‐m diameter) mixed flow pump survived but 96.5% had minor injuries, reduced physical condition and/or abnormal behaviour. By contrast, 64.7% of PIT‐tagged eels recaptured ( n = 17) downstream of a small (0.8‐m diameter) axial flow pump died. No acoustic‐tagged eels that passed through the small axial flow pump ( n = 10) performed onward migration at sea, unlike "control" eels released downstream ( n = 11). This evidence may help develop effective remediation measures, such as operational changes, to maximise escapement of catadromous eel species at pumping stations.